The influence of clinical characteristics, laboratory and inflammatory markers on ‘high on-treatment platelet reactivity’ as measured with different platelet function tests - Elsenberg, Ellen H. A. M.; van Werkum, Jochem W.; van de Wal, Ruud M. A.; Zomer, Carla A.; Bouman, Heleen J.; Verheugt, Freek W. A.; ten Berg, Jurriën M.; Hackeng, Christian M. (Thrombosis and Haemostasis, 2009)
High on-clopidogrel platelet reactivity (HCPR) and high on-aspirin platelet reactivity (HAPR) are independently associated with an increased risk of atherothrombotic events. However, despite this positive correlation, the definitions of both HCPR and HAPR vary largely throughout studies and between different platelet function assays.The aim of the present study was to explore clinical and laboratory parameters that are associated with HCPR and HAPR as measured with different platelet function tests. 530 clopidogrel and aspirin pre-treated patients undergoing elective PCI (percutaneous coronary intervention) were enrolled. Platelet function measurements were performed with: optical aggregometry, the VerifyNow device and PFA-100 cartridges (including the novel INNOVANCE® P2Y assay). HCPR as measured with Adenosin-Di-Phospate-induced (ADP) aggregation based tests was associated with clinical factors such as older age, female gender and Diabetes mellitus (DM).TheVerifyNow P2Y12 assay was significantly influenced by haemoglobin and haematocrit levels. HAPR as measured with aggregation based tests was significantly influenced by the presence of malignancy, BMI (Body-Mass Index), older age and increased levels of hsCRP (high sensitivity c-reactive proteine).The PFA-100 COL/ EPI (collagen-epinephrine) and COL/ADP (collagen-ADP) cartridges were significantly influenced by monocyte count,hs-CRP, MPV (mean platelet volume), vWF-antigen (von Willebrand factor) and vWF-activity. HCPR as measured with the novel INNOVANCE® P2Y cartridge was associated with clinical determinants such as BMI,female gender,impaired LVEF (left ventricular ejection fraction), renal failure and dosing of clopidogrel. Laboratory markers that were associated with HCPR as measured with INNOVANCE® P2Y were platelet count, white blood cells (WBC), hsCRP and fibrinogen.Both HCPR and HAPR are highly dependent on the type of platelet function assay. Each platelet function assay, in turn, is significantly influenced by distinct clinical and laboratory variables.
Keywords: High on-treatment platelet reactivity; clopidogrel; aspirin; platelet function testing